The morphological investigations on the intestines of akkaraman sheep and ordinary goats - İ. Enver OZAN (Eurasian Journal of Veterinary Sciences)
This study has been done on fourty mature sheep and goats, twenty from each groups. Macroscopic and• microscopic structures of their intestines were examined. Fresh and formaldehyde preserved examples- were used in macroscopic studies. Length and diamaters of fresh intestines were measured. In addition, their volumes were determined by filling them with water. The length of intestines were compared to the length of body and mean percantage determined. The results were- reported on the table. For microscopic examinations, microscopic slides were prepared from certain si tes of intestines. Villi, glandulae and another structures were examined.